2010
DOI: 10.1002/mc.20633
|View full text |Cite
|
Sign up to set email alerts
|

Association between TP53 gene ARG72PRO polymorphism and chromosome aberrations in human cancers

Abstract: It is well known that the TP53 gene considerably influences on DNA repair processes. Polymorphisms in the TP53 gene, particularly the well-known Arg72Pro in codon 72 of exon 4 (Ex4+119 G>C; rs1042522), can modify the functionality of the p53 protein and activation of DNA repair. Actually, polymorphic variants Arg and Pro were found to have different properties of regulation of TP53-dependent DNA repair target genes, that can effect various levels of chromosome aberrations in cancer patients with these genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Siddique & Sabapathy 21 reported that Pro-expressing cells exhibit reduced micronuclei formation compared to Arg-expressing cells. Later, Litviakov 33 showed that cancer patients with Pro/Pro genotype have fewer chromatid breaks in comparison to Arg/Pro and Arg/Arg carriers. Moreover, chromosomal radiosensitivity, as measured by the G2-chromosome break assay, has been reported to be associated with polymorphisms in TP53 codon 72 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Siddique & Sabapathy 21 reported that Pro-expressing cells exhibit reduced micronuclei formation compared to Arg-expressing cells. Later, Litviakov 33 showed that cancer patients with Pro/Pro genotype have fewer chromatid breaks in comparison to Arg/Pro and Arg/Arg carriers. Moreover, chromosomal radiosensitivity, as measured by the G2-chromosome break assay, has been reported to be associated with polymorphisms in TP53 codon 72 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The variant Pro allele has been shown to be less efficient in suppressing cell transformation and inducing apoptosis and to be less sensitive to degradation by viral oncogenic proteins (11). However, other recent reports have pointed out that the Arg variant is a less efficient DNA repair molecule and therefore Arg/Arg carriers may have an increased frequency of chromosomal aberrations and a high level of genomic instability (34,35). …”
Section: Discussionmentioning
confidence: 99%
“…For example, the TP53 tumor suppressor gene is mutated in >50% of human tumors [42]. Among the 393 amino acids of P53, sequences at positions 5-28 have p53 transcription activity and pathogenic mutations are enriched at R248Q, R273H, and R282W which affect DNA binding, or in R175H, Y220C, G245S, and R249S which are called conformational mutations [43,44]. The mechanism of p53 in cancer development has been thoroughly investigated, with more than 70K papers published since 1979.…”
Section: Loss Of Heterozygosity Provides Novel Therapeutic Targets For Cancer Treatmentmentioning
confidence: 99%